2015
DOI: 10.1002/jmr.2464
|View full text |Cite
|
Sign up to set email alerts
|

A selectivity study of sodium-dependent glucose cotransporter 2/sodium-dependent glucose cotransporter 1 inhibitors by molecular modeling

Abstract: Sodium-dependent glucose cotransporters (SGLTs) play an important role in glucose reabsorption in the kidney and have been identified as promising targets to treat diabetes. Because of the side effects like glucose and galactose malabsorption by targeting SGLT1, highly selective SGLT2 inhibitors are more promising in the treatment of diabetes. To understand the mechanism of selectivity, we conducted selectivity-based three-dimensional quantitative structure-activity relationship studies to highlight the struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 56 publications
1
6
0
1
Order By: Relevance
“…The predicted increase in hydrophobicity due to increased secondary structural contents (helices H1, 2 and 3) may promote high specificity and strong affinities of Pz or its analogs for SGLT2-PBD as compared to SGLT1. These assumptions fit quite nicely with the recently illustrated homology modeling and molecular dynamics simulation studies predicting higher stability of SGLT2 binding complexes than SGLT1 [39]. Hydrogen bond analysis and binding free energy calculation revealed the importance of structural components of SGLT2 that seem to be different in SGLT1 [39] further suggesting that increases in hydrophobicity of SGLT2-PBD, presumably via H1, H2 and H3 helical structures, might promote hydrogen bonding within the binding pocket and upon inhibitor binding.…”
Section: Discussionmentioning
confidence: 56%
“…The predicted increase in hydrophobicity due to increased secondary structural contents (helices H1, 2 and 3) may promote high specificity and strong affinities of Pz or its analogs for SGLT2-PBD as compared to SGLT1. These assumptions fit quite nicely with the recently illustrated homology modeling and molecular dynamics simulation studies predicting higher stability of SGLT2 binding complexes than SGLT1 [39]. Hydrogen bond analysis and binding free energy calculation revealed the importance of structural components of SGLT2 that seem to be different in SGLT1 [39] further suggesting that increases in hydrophobicity of SGLT2-PBD, presumably via H1, H2 and H3 helical structures, might promote hydrogen bonding within the binding pocket and upon inhibitor binding.…”
Section: Discussionmentioning
confidence: 56%
“…С учетом локализации SGLT1 на эпителии тонкой кишки и потенциального риска развития диспепсиче-ских побочных эффектов при ингибировании SGLT1, клинически значимо соотношение селективности IC 50 SGLT1/IC 50 SGLT2 [26], максимальное из которых соот-ветствует эмпаглифлозину.…”
Section: эмпаглифлозин -высокоселективный ингибитор Sglt2unclassified
“…Previous studies have indicated that the hSGLT2 inhibitors fit into the binding site of hSGLT2 by interacting with several important residues, such as Asn75, His80, Glu99, Ala102, Arg267, Tyr290, Trp291, Gln457, and Pro518 [55] [56] [57] [58]. Among these important residues, Asn75, Glu99, Arg267, and Tyr290 are the most essential key residues since they form a hydrogen bonding network with hSGLT2 inhibitors [55] [56] [57] [58]. According to the above screening criteria, only 1 N-glycoside and 4 non-glycoside compounds were finally identified to be potential hSGLT2 inhibitors (Table 5).…”
Section: Molecular Dockingmentioning
confidence: 99%